An environmentally friendly strategy for cadaverine bio-production: in situ utilization of CO2 self-released from L-lysine decarboxylation for pH control. Issue 37 (April 2020) - Wei, Guoguang; Zhang, Alei; Lu, Xuedong; He, Feng; Li, Hui; Xu, Sheng; Li, Ganlu; Chen, Kequan; Ouyang, Pingkai
Graphical abstract: Highlights: The CO2 self-released from L-lysine decarboxylation can completely replace the use of acids for pH control with less cell damage and simple process. The scale up (3000 L reactor) of protocol using the CO2 as pH control was feasible with a higher cadaverine concentration and shorter conversion time. Ca(OH)2 was chosen to free cadaverine and remove SO4 2+, which was beneficial to cadaverine purification. The cadaverine with a high purity of 99.82% and recovery of 72.29% were obtained by two-step distillation without extraction. Abstract: In this study, we propose a novel in situ pH control method for bio-production of cadaverine. The CO2 released from l -lysine decarboxylation in whole cell catalysis process was used to adjust the pH of the conversion system via sealing the reactor. The results showed that the self-released CO2 can well control the pH of the conversion system below 7.5 in the whole process, when the pressure of a reactor was maintained at 0.2 Mpa. Meanwhile, the system using self-released CO2 as pH control possess better ability of cadaverine production with less cell damage, compared with that of using HCl. The optimal conditions for cadaverine production using self-released CO2 as pH control were an initial concentration of l -lysine of 300.0 g/L, pyridoxal-5-phosphate of 0.15 mM, rotation of 300 rpm, time of 180 min, and resulting cadaverine of 208.2 g/L with 99.33 % conversion ratio of the substrate l -lysine. Furthermore, the protocol can be scaled up to a 3000 L reactor with similar yield and shorter conversion time (120 min) under optimized conditions, compared with that (180 min) of 7.5 L fermenter. Additionally, cadaverine of high purity (99.82 %) with recovery of 72.29 % was obtained by purification. This new approach provided a green and efficient method for industrial bio-production of cadaverine without the use of acids or other environmentally unfriendly reagents.